2018
DOI: 10.5603/aa.2018.0017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the healing progress of phlegmon related to type 2 diabetes treated with the local hyperbaric oxygen therapy

Abstract: Introduction. Phlegmon is a disease which causes purulent inflammation of the subcutaneous tissue, being of unlimited character. This disease does not only affect the external coverings of the body; it may also be transmitted to the internal organs, and lead to their insufficiency. Case report. The study presents the results of the physical therapy applied to phlegmon located in the right shank and foot of a 57-year old patient with type 2 diabetes after an ineffective typical symptomatic treatment. A local hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…[15][16][17]44,45 So far, the therapeutic efficacy of both presented methods in the treatment of leg ulcers of various origin has been observed in some published case histories. 4,[19][20][21]46 In the present study, we confirmed for first time that the application It should be emphasized that the time required for a single procedure and the number of procedures in the therapeutic cycle were similar for both analyzed therapeutic modalities.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…[15][16][17]44,45 So far, the therapeutic efficacy of both presented methods in the treatment of leg ulcers of various origin has been observed in some published case histories. 4,[19][20][21]46 In the present study, we confirmed for first time that the application It should be emphasized that the time required for a single procedure and the number of procedures in the therapeutic cycle were similar for both analyzed therapeutic modalities.…”
Section: Discussionsupporting
confidence: 74%
“…[37][38][39][40] In case of LASEROBARIA-S device, the regenerative effect of HBO treatment is additionally supported by the activity of variable magnetic field having physical parameters used in magnetotherapy, as well as the activity of low-energy light emitted by LEDs. 18,19 Among the mechanisms of regenerative effect of extremely low- In case of therapy with the use of LASEROBARIA-S device, the analgesic effect of HBO is additionally boosted by the activity of alternating magnetic field, with physical parameters applied in magnetotherapy, as well as by low-energy light radiation emitted by LEDs. 6 In the mechanism of analgesic activity of alternating magnetic fields having low frequency, a substantial role is, among others, that of stimulation of release of endorphins and NO being a transmitter in nerve fibers, which transmit pain stimuli, anti-inflammatory, and antioedematic activities, as well as local improvement in blood supply to tissues in the ulceration area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations